REFLEKSJE NA TEMAT ŻĄDAŃ ODSZKODOWAWCZYCH ZABUŻAN Z TYTUŁU UTRATY MIENIA NA KRESACH WSCHODNICH W ŚWIETLE PRAWA MIĘDZYNARODOWEGO I PRAWA POLSKIEGO - Łaski, Piotr (Wydział Prawa i Administracji UAM, 2002)
The years 1943 and 1945 marked the two waves of displacing residents of the eastern borderlands of Poland, forcing the people to abandon their real estate in the areas that no longer belonged to Poland. The Author discusses the moral and legal implications of the displacement, focusing on the legal regulations in Poland, under communism and beyond, depicting the political tendencies regarding the displaced population in the communist Poland. Additionally, an analysis is proposed of the international treaties ratified by Poland and the ensuing obligations, as well as the issue of courts’ reluctance to hear cases of the repatriates’ claims for damages. The article is wrapped up by the sad conclusion that until the present time this group of people has been given no opportunity to regain any compensation due for the property they were deprived of.
REMARKS UPON THE CLAIMS FOR DAMAGES MADE BY FORMER INHABITANTS OF POLISH TERRITORIES BEYOND THE BUG RIVER IN THE LIGHT OF THE INTERNATIONAL AND POLISH LAW